The main conceptions of interest representation in the political process - Малявін, Є. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article deals with the classical and modern theories of political representation. The classic conceptions of interest representation in the political process are considered, whose theoretical elaboration belongs to such authors as J. Locke, S.L. Montesquieu, A. de Tocqueville, J.S. Mill, E. Burke, etc. The modern models of political representation are structured taking into consideration more recent political theories, fathered by K. Marx, M. Duverger, P. Bourdieu, G. Almond, S. Verba, S. Lipset, C. Rocken, J. Wiatr, E. Heywood, etc. Special attention is paid to the role of political parties in the political interests’ representation.